REVOLUTIONIZING EDUCATION: THE ROLE OF PEDAGOGY IN MODERN EDUCATION AND TEACHING - Eshmonova, Sevinch (Science technology&Digital finance, 2023)
This article examines the importance of pedagogy in modern education and teaching and how it can be used to change the educational system as we know it.